Botanical Antifeedants: An Alternative Approach to Pest Control - Pavela, Roman; Kovaříková, Kateřina; Novák, Matěj (Insects, 2025)
Plant protection against phytophagous pests still largely relies on the application of synthetic insecticides, which can lead to environmental and health risks that are further exacerbated by the development of resistant pest populations. These are the driving forces behind the current trend of research and the development of new ecological insecticides. The mode of action does not have to rely exclusively on acute or chronic toxicity. Another promising approach is the use of plant antifeedants, which can significantly reduce the food intake of phytophagous insects. However, the information on antifeedant substances has not yet been sufficiently evaluated. The aim of this review was to find the most promising plants that provide potent extracts, essential oils (EOs), or isolated compounds with antifeedant properties. The selection was based on a comparison of effective concentrations or doses. Effective extracts were obtained from 85 plant species belonging to 35 families and the EOs came from 38 aromatic plant species from 11 families. Based on the results, Angelica archangelica, Caesalpinia bonduc, Grindelia camporum, Inula auriculata, Lavandula luisieri, Mentha pulegium, Piper hispidinervum, and Vitis vinifera were selected as promising plants with antifeedant potential. These plants are potent antifeedants, and at the same time provide sufficient biomass for industrial use in the development and production of botanical antifeedants.
Keywords: plant extracts; pests; antifeedant activity; phytophagous; essential oils; compounds